RETRACTED: Ernest Hemingway’s A Farewell to Arms: A Critical Study of War and Its Negative Impact from An Ironic Perspective - Muhammad Dera Farhan Al-Fahdawi (Pascasarjana UM, 2017)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Humaniora to article entitled “Ernest Hemingway’s A Farewell to Arms: A Critical Study of War and Its Negative Impact from An Ironic Perspective